Feminist Concern in R.K Narayan's Novel "The Guide" (Journal of Advances and Scholarly Researches in Allied Education, 2021)
R.K. Narayan, one of the popular and most popular scholars on the planet. He is known for his basic and humble language utilization. The greater parts of his novels uncover the dominance over the women where he displays his feministic sees. In this work, I should portray the portrayal of women and their status in the Indian society with one of Narayan's novels 'The Guide' distributed in 1958, which is the most acclaimed novel of R. K. Narayan that won him colossal notoriety as well as the Sahitya Academy Award for 1960.In his novel he needed to foster an alternate arrangement of laws through which the denied women of the society would be liberated from the male subjugation. This paper shows how his women break the customarily acknowledged traditions about women's status in India and revamp a new status to set up them as human creatures in their own light.